Renewable Energy Storage System Based on a Power-to-Gas Conversion Process. (November 2016) - Ancona, M.A.; Antonioni, G.; Branchini, L.; De Pascale, A.; Melino, F.; Orlandini, V.; Antonucci, V.; Ferraro, M.
Abstract: The increasing penetration of renewable energy generation in the electric energy market is currently posing new critical issues, related to the generation prediction and scheduling, due to the mismatch between power production and utilization. In order to cope with these issues, the implementation of new large scale storage units on the electric network is foreseen as a key mitigation strategy. Among large scale technologies for the electric energy storage, the Power-to-Gas solution can be regarded as a long-term viable option, provided that the conversion efficiency is improved and aligned with other more conventional storage alternatives. In this study, a Power-to-Gas storage system is investigated, including as main components a high-temperature electrolyzer for hydrogen generation and a Sabatier reactor for methane production. The high-temperature Solide Oxide Electrolyser Cell (SOEC) technology, currently under development, is considered as a promising solution for hydrogen generation, due to the expected higher efficiency values, in comparison with conventional low-temperature electrolysis technologies. In order to evaluate the performance of the system and the energy efficiency, in this study a numerical model of the SOEC integrated with the Sabatier reactor has been implemented, including also the necessary additional auxiliaries, which can significantly affect the energy conversion performance. The whole energy conversion and storage system has been analyzed, taking into account different layout variants, by means of Aspen Hysys TM numerical tool, based on a lumped modelling approach. The various Power-to-Gas storage configurations have been compared, with the aim to optimize both the system's efficiency and the composition of the produced gas stream.